Inherent atomic mobility changes in carbocation intermediates during the sesterterpene cyclization cascade - Sato, Hajime; Mitsuhashi, Takaaki; Yamazaki, Mami; Abe, Ikuro; Uchiyama, Masanobu (Beilstein Journal of Organic Chemistry, 2019)
We previously showed that the regio- and stereoselectivity in terpene-forming reactions are determined by the conformations of the carbocation intermediates, which reflect the initial conformation of the substrate, geranylfarnesyl diphosphate (GFPP). However, it remains unclear how the initial conformation of GFPP is controlled, and which part(s) of the GFPP molecule are important for its fixation inside the substrate-binding pocket. Here, we present the first detailed analysis of the inherent atomic mobility in carbocation intermediates during sesterterpene biosynthesis. We identified two methyl groups as the least mobile of all the carbons of the carbocation intermediates in the first half of the cyclization cascade. Our analysis suggests that these two methyl groups are critical for the preorganization of GFPP in the biosynthetic pathways leading to sesterfisherol and quiannulatene.
Keywords: biosynthesis; carbocation; DFT; substrate recognition; terpene cyclase